FROM A FEMALE TO A MALE TRADITION: THE BATIK SARONG FROM THE PERSPECTIVE OF THE SOCIOLOGY OF ISLAMIC RELIGIOUS EDUCATION IN PAMEKASAN, MADURA - Marsum Marsum; Zainuddin Syarif; Syaiful Anam (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to examine the shift in the meaning and use of batik sarongs, from a tradition initially associated with women to a more dominant identity used by men in Madurese society, particularly in the Pamekasan region. This change is analyzed through the perspective of the sociology of Islamic religious education, emphasizing the role of religion, local culture, and the educational process in shaping gender identity. This study uses a qualitative approach using interview, observation, and documentation study methods. The results show that batik sarongs are no longer only understood as a symbol of traditional culture, but also as a symbol of piety, modesty, and male religious identity, especially in the context of Islamic boarding schools and Islamic education. This shift is influenced by the process of internalizing Islamic values ​​through formal and non-formal education, as well as a reinterpretation of dress norms in Madurese society. This study concludes that the changing use of batik sarongs reflects the dynamic interaction between culture, religion, and education in shaping the construction of gender identity in Madurese Muslim society.